Valgus impacted proximal humeral fractures and their blood supply after transosseous suturing - Panagopoulos, Andreas M. (Springer-Verlag, 2004)
We treated 16 patients (11 women and five men, average age 45 years), all having four-part valgus impacted fractures of the proximal humerus, with transosseous suturing. All had preoperative angiography performed 6–12 h after admission. The average impaction angle was 43°, and the mean lateral displacement of the humeral head was 1.4 mm. Postoperative angiography was performed 8–10 weeks after the operation followed by digital image processing using the segmentation technique. No statistically important reduction in the length and area of large (>0.5 mm) vessels was seen. Union was confirmed by the reduction in the length and area of small vessels (<0.5 mm). At a mean follow-up of 40 months, avascular necrosis was only found in one patient. The average Constant–Murley score was 87 (67–100) points, whereas the functional score in comparison with the unaffected shoulder was 94% (89–100%). Despite the small number of patients, transosseous fixation seems to preserve the remaining blood supply of the humeral head.